Short Term Comparison Between Safety and Efficacy of Rosuvastatin 40 mg and Atorvastatin 80 mg in Patients with Acute Coronary Syndrome - Sh. A. Mostafa; Kh. Elrabat; M. Mahrous; M. Kamal (Рациональная фармакотерапия в кардиологии)
Background. Dyslipidemia is one of the most serious modifiable risk factors for acute coronary  syndrome which is the most leading cause of mortality and morbidity worldwide.Aim. To assess the short-term safety and efficacy of full dose rosuvastatin and atorvastatin in patients with acute coronary  syndrome.Material and methods. Single center, prospective, randomized study included 100 patients who were randomized from first 24-hour of admission to either atorvastatin 80  mg  daily (group 1) or rosuvastatin 40  mg  daily (group 2). Primary outcomes included levels of inflammatory markers (erythrocyte sedimentation rate [ESR], high-sensitive C-reactive protein [hs-CRP] and total leukocyte count [TLC]) after 4 weeks of treatment and lipid profile after 3 months. Secondary  outcomes included recurrent myocardial infarction, recurrent angina, stroke and side effects.Results. At admission, both groups  were comparable in age, without statistically significant difference regarding risk factors (diabetes, hypertension, smoking and obesity), echocardiography (end-diastolic volume, end-systolic volume and ejection fraction), laboratory parameters of inflammation and lipid profile. After 1 month, there was insignificant difference between rosuvastatin and atorvastatin in the reduction of ESR, Hs-CRP or TLC. After 3 months rosuvastatin showed statistically significant reduction in the level of low-density lipoprotein cholesterol, triglyceride (p<0.001) and significant increase in high-density lipoprotein cholesterol (p<0.001) when compared to atorvastatin and at the same time the rosuvastatin group  was safer regarding liver enzymes elevation, p<0.001 for alanine and p<0.01 for aspartate aminotransferases, respectively.Conclusions. Our findings demonstrated that  rosuvastatin 40  mg/day is safer and more effective than  the atorvastatin 80  mg/day in the terms  of lipid parameters and inflammatory biomarkers.